Interconnection between Structural-Functional Families as Nafkah Provider and Common Property Concept under Indonesian Family Law Regulations: Interkoneksi Struktural-Fungsional Penanggung Jawab Nafkah dan Konsep Harta Bersama dalam Regulasi Hukum Keluarga Indonesia - Juanda, Vian (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This study aims to examine the structural-functional family as nafkah provider normatively and empirically. Empirically and interconnect it with common property concept under Indonesian family law regulations, in this case Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. This topic is interesting to discuss because in the reality of society there are structural-functional variations of the family that are not in harmony with family law regulations in Indonesia and as a means of providing knowledge about the implications of common property in such cases. The research method used was a field study by interviewing several families with length of marriage over 10 years serving as a nafkah provider. As a result, there are three variations of nafkah provider, namely the husband as a provider, the wife as a provider, the husband and wife collaborate as providers. The structural-functional interconnection of nafkah provider normatively and empirically has been polemical because there are facts in society that are regarded that it is not relevant to Indonesian family law regulations. However, in the common property concept, which is property acquired during marriage, structural-functional interconnection in family does not affect the status of common property. Thus, common property remains a common right regardless of who works and acts as provider in family unless there is a court verdict that considers it in a fair context.